PENGARUH PEMBERDAYAAN PEREMPUAN TERHADAP PEMBANGUNAN PARIWISATA BERKELANJUTAN DI PROVINSI SULAWESI UTARA - Salina, Marchella Gabiel; Firman, Afrizal; Maichal, Maichal (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.03.TAHUN.2025DO - 10.24843/EEB.2025.v14.i03.p06, 2025)
Tourism is widely developed in every country in the world, including Indonesia. North Sulawesi Province is one of the provinces that has potential in the tourism sector. This study analyzes the influence of women's empowerment from economic, social, environmental, and psychological aspects toward sustainable tourism development in North Sulawesi Province. The method used in this study is PLS-SEM (partial least squares - structural equation modeling). Types of data using primary data with data collection techniques through interviews and distributing questionnaires directly through physical and Google Forms. The study population is all women who have businesses related tourism sector, with a total sample of 77 respondents. The sampling technique based on considerations (purposeful sampling). The results of the study, two variables do not have an effect, that is economic empowerment and social empowerment, which doesn’t affect toward sustainable tourism development. Two variables have an effect, namely environmental empowerment, and psychological empowerment, which have a substantial effect toward sustainable tourism development. This study contributes impact of tourism industry development theoretically and practically, especially on the findings that occur in the North Sulawesi Province.